Ploščatocelični karcinom ustne votline in ustnic - Kansky, Andrej (Radiology and oncology (Ljubljana), 1999)
Squamous cell carcinoma of the oral cavity and the lip present about 6% of allcancers diagnosed each year and about 30% of all head neck cancers. The relationship beetwen tobacco exposure, alcoholabuse and poor dental hygiene and disease developement has been clearly proportional demonstrated. A clear dose-response relationship has been identified with a greater risk being directly proportional to intensity and duraton of exposure. Other possible etiologic agents are being investigated. Prognostic evaluation is based on clinical staging of the tumor, on histologic characteristic of the primary tumor and the lymph nodes. Selection of the therapy depends on multiple factors; three major types of therapeutic modalities are avaible; surgery, radiation and a combination of both surgery and radiation. The lip is the mostcommon site in the cancer of the head and neck. The majority of these lesions occur on the lower lip and males. A principal ethiologic factor is sunexposure and use of tobaco. The prognosis is better, compared to other forms of oral carcinoma. Surgery is the mainstay of therapy.
Keywords: Carcinoma; diagnostika; karcinom; Lip neoplasms; Mouth neoplasms; Neoplasm staging; rak (medicina); ustna votlina; ustnice; zdravljenje